2022
DOI: 10.1136/jitc-2022-004656
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of camrelizumab plus apatinib during the perioperative period in resectable hepatocellular carcinoma: a single-arm, open label, phase II clinical trial

Abstract: ObjectiveThis study aimed to assess the efficacy and safety of camrelizumab plus apatinib in patients with resectable hepatocellular carcinoma (HCC) as neoadjuvant therapy.MethodsInitially, 20 patients with HCC were screened and 18 patients with resectable HCC were enrolled in this open-label, single-arm, phase II clinical trial. Patients received three cycles of neoadjuvant therapy including three doses of camrelizumab concurrent with apatinib for 21 days followed by surgery. Four to 8 weeks after surgery, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 68 publications
5
45
0
1
Order By: Relevance
“…The incidence of TRAEs in this study was consistent with the published data (27)(28)(29)(30). TACE-AP and TACE-A are safe, and the adverse reactions are tolerable.…”
supporting
confidence: 91%
“…The incidence of TRAEs in this study was consistent with the published data (27)(28)(29)(30). TACE-AP and TACE-A are safe, and the adverse reactions are tolerable.…”
supporting
confidence: 91%
“…Ten HCC patients were treated with anti-PD1. Biopsy samples were sequenced with 289 nanostring panel RNA before treatment, and the response (≥50% tumor necrosis) (R) and non-response (<50% tumor necrosis) (NR) were compared ( 14 ). In contrast to non-responsive tumors, biopsy of responsive tumors showed higher transcription levels of CD244, CD274, CCL13, IDO1, CD70, IL12RB2, CD19, IL4, and lower transcription levels of UBB and GUSB ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…IFNα and anti-PD1 cotreatment as a novel combination strategy for HCC has also been suggested [10]. A recent study demonstrated that perioperative camrelizumab plus apatinib displays promising e cacy and manageable toxicity in patients with resectable HCC [27]. However, the bene ts of immunotherapy are limited in certain patients.…”
Section: Discussionmentioning
confidence: 99%